2021
DOI: 10.48550/arxiv.2109.07942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SN 2018bsz: significant dust formation in a nearby superluminous supernova

Abstract: We investigate the thermal emission and extinction from dust associated with the nearby superluminous supernova (SLSN) 2018bsz. Our dataset has daily cadence and simultaneous optical and near-infrared coverage up to ∼100 days, together with late time (+1.7 yr) MIR observations. At 230 days after light curve peak the SN is not detected in the optical, but shows a surprisingly strong near-infrared excess, with r − J > 3 mag and r − K s > 5 mag. The time evolution of the infrared light curve enables us to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 118 publications
5
36
0
Order By: Relevance
“…Radio and millimetre observations have mostly found non-detections (Law et al 2019;Murase et al 2021;Eftekhari et al 2021;Hatsukade et al 2021a), but three sources have been detected: PTF10hgi (Eftekhari et al 2019;Law et al 2019;Mondal et al 2020;Hatsukade et al 2021b), which is consistent with the magnetar model; SN2017ens (Coppejans et al 2021a), which may be either due to a magnetar or CSM shock; and 2020tcw (Coppejans et al 2021b), which was detected only months after explosion and is likely due to CSM interaction. An infrared excess in magnetar-driven supernova was predicted by Omand et al (2019) due to heating of dust formed in the supernova, and which was observed recently in SN2018bsz (Chen et al 2021).…”
Section: Introductionmentioning
confidence: 65%
“…Radio and millimetre observations have mostly found non-detections (Law et al 2019;Murase et al 2021;Eftekhari et al 2021;Hatsukade et al 2021a), but three sources have been detected: PTF10hgi (Eftekhari et al 2019;Law et al 2019;Mondal et al 2020;Hatsukade et al 2021b), which is consistent with the magnetar model; SN2017ens (Coppejans et al 2021a), which may be either due to a magnetar or CSM shock; and 2020tcw (Coppejans et al 2021b), which was detected only months after explosion and is likely due to CSM interaction. An infrared excess in magnetar-driven supernova was predicted by Omand et al (2019) due to heating of dust formed in the supernova, and which was observed recently in SN2018bsz (Chen et al 2021).…”
Section: Introductionmentioning
confidence: 65%
“…With the deprecation of Python 2 and popular photometry packages within IRAF, AutoPhOT provides accurate photometry with little User setup or monitoring. AutoPhOT has already been used in several scientific publications (Chen et al 2021, Fraser et al 2021, Brennan et al 2021a, Brennan et al 2021b at the time of writing.…”
Section: Conclusion and Future Developmentmentioning
confidence: 99%
“…This phenomenon also extends to H-poor SLSNe (SLSNe-I). For example, iPTF13ehe, iPTFesb, iPTF16bad, iPTF16eh, SN 2018bsz, and other events discussed in Hosseinzadeh et al (2021) show evidence of CSM material located ∼ 10 16 cm from their explosion sites (Yan et al 2017;Lunnan et al 2018;Anderson et al 2018;Chen et al 2021;Pursiainen et al 2022).…”
Section: Introductionmentioning
confidence: 98%